1985
DOI: 10.1002/jor.1100030312
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of phasic muscle activity: Performance of surface and intramuscular wire electrodes in gait analysis

Abstract: Repeatability is an important consideration for gait analysis data that are being used as an adjunct to clinical decision making. An index of repeatability may be based on a statistical criterion (variance ratio) that reflects similarity of wave forms over a number of identical cycles. The purpose of this study was to use the variance ratio to assess the repeatability of phasic muscle activity recorded with surface and bipolar intramuscular wire electrodes during gait on 10 normal subjects. Variance ratios wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 12 publications
(5 reference statements)
5
67
1
Order By: Relevance
“…It also has been found that the reliability of the surface EMG signal is better than analyzing activity with intramuscular fine-wire electrodes. 17,21,27 However, cross-talk may be a limitation when using surface electrodes during EMG recordings, especially when analyzing small muscles. 16,45 We feel that crosstalk was not a significant problem in this study because we analyzed large superficial muscles.…”
Section: Limitationsmentioning
confidence: 99%
“…It also has been found that the reliability of the surface EMG signal is better than analyzing activity with intramuscular fine-wire electrodes. 17,21,27 However, cross-talk may be a limitation when using surface electrodes during EMG recordings, especially when analyzing small muscles. 16,45 We feel that crosstalk was not a significant problem in this study because we analyzed large superficial muscles.…”
Section: Limitationsmentioning
confidence: 99%
“…The speed of jogging at which the EMG activity was recorded in the three conditions was freely chosen by the subjects because previous research (e.g., Kadaba et al 1985) have shown that EMG activity is more reproducible when the speed is chosen freely than when it is imposed.…”
Section: Discussionmentioning
confidence: 99%
“…The electrodes chosen for the study were of surface type, because they have the following advantages over intramuscular ones: do not cause pain or bleeding, are easier to apply, and as shown by Kadaba et al (1985), they provide a more reproducible signal than that obtained with intramuscular electrodes.…”
Section: Emgmentioning
confidence: 99%
“…In the study, the frequency of vibration was determined for each member by monitoring the EMG RMS activity of the vastus lateralis muscle during trials performed at different frequencies; no vibration (i.e. 0 Hz), and at 20,25,30,35,40,45,50, and 55 Hz. These were administered in random order with a 4-minute pause between trials with each subject experiencing vibration for 20-seconds.…”
Section: Individualized Frequenciesmentioning
confidence: 99%
“…Electrodes placed on the surface of the muscle records the sum of all motor unit action potentials being transmitted along the muscle fibers under the electrode at a given time providing a numerical value output. Surface electrodes, as with indwelling electrodes, can both detect the average activity of superficial muscles although surface electrodes have been shown to produce more reproducible results than indwelling electrodes [50]. Surface EMG is currently considered a more acceptable way to record EMG as it is practical and requires a less intricate and invasive set up [51].…”
Section: Electromyography (Emg)mentioning
confidence: 99%